2018
DOI: 10.1634/theoncologist.2017-0574
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of First-Line Systemic Treatment for Unresectable Conventional, Dedifferentiated, Mesenchymal, and Clear Cell Chondrosarcoma

Abstract: Currently, there are no uniform treatment lines for advanced chondrosarcoma patients, which results in a very diverse group of treatment regimens being used. In this study, the data of 112 patients was collected. It was concluded that some treatment regimens seem to have a better progression-free survival compared with others, and that these results also differ between the chondrosarcoma subtypes. Prospective studies need to be conducted based on preclinical work to develop a uniform regimen to treat advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…Aside from cisplatin, doxorubicin is one of the most commonly used anti-tumor agents in chondrosarcoma chemotherapy 48,49 .…”
Section: Resultsmentioning
confidence: 99%
“…Aside from cisplatin, doxorubicin is one of the most commonly used anti-tumor agents in chondrosarcoma chemotherapy 48,49 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, however, the limited data on the response to neoadjuvant chemotherapy in our series only indicated a relative resistance of DDCS to most classical anti-bone sarcoma drugs. Several studies have indicated that ifosfamide-based adjuvant chemotherapy [8] or doxorubicin monotherapy [22] may offer survival benefit for patients with DDCS. In our series, the combination of doxorubicin and cisplatin was found significantly associated with delayed disease progression.…”
Section: Sarcomamentioning
confidence: 99%
“…Complete en bloc surgical resection is the gold standard treatment and should be offered whenever feasible. Generally, chondrosarcoma is chemo-and radiation-resistant, and the treatment of advanced disease poses a huge clinical challenge [25,26].…”
Section: Current Therapeutic Approaches In Chondrosarcomamentioning
confidence: 99%